Lecture Notes in Nutrition for Students of Nursing and Medicine - Virk RS, Kapilashrami MC; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2000)
The book "Lecture Notes in Nutrition" aims at covering some of the vital topics of food and nutrition. This book play important role of food and nutrition in the health for students of nursing and medicine. In this book a number of good and elaborate texts on the subject are available, though few cater to the specific requirements of the young student of medicine and nursing during their first exposure to the subject, including Community Nutrition. The Lecture Notes make an attempt to bridge this gap and facilitate quick and correct learning. The format of the Notes in its simplicity tries to address the needs of the students by providing comprehensive information of the current concepts, so as to facilitate understanding and enable the practice of scientifically tested healthy nutritional practices. This book will provide a concise reference source and meet the requirements of the students of Nutrition and other Health professionals working in this field.
Keywords: Nutrition and Dietetics; Electronic books